Effect of empty fruit bunch compost on the performance of tomatoes (Lycopersicum esculentum) grown on Bungor Series - Othman, Abdul Haziq Qayyum (2015)
Empty Fruit Bunch (EFB) originates from an oil palm industry as a by-product, and used widely as EFB compost in soil amendment practices. EFB compost contains macro-micro nutrients (N, P, and K) that are beneficial to crops; therefore, the main objectives of this study were: i) to evaluate tomato growth performance under Bungor Series with different rate of EFB and, ii) to evaluate the optimum rate of EFB compost in tomato cultivation. In this study, tomatoes (Lycopersicum esculentum) from Serdang 2 variety was planted at Ladang 2, Universiti Putra Malaysia in a polybag (12cm × 20cm) under a shaded area. The experiment was conducted in Latin Square Experimental Design (LS) with four replication and four treatment (EFB compost rates) thus, a total of 16 experimental unit. The rates of EFB that were applied are 0 g (control), 20 g, 40 g, and 60 g. Each treatment was given the same amount of NPK fertilizers that consists of urea, rock phosphate and muriate of potash. Before EFB compost was mixed in the field of study, 16 soil samples were collected for determination of physical and chemical properties. In vegetative stage and after harvest of tomato, soil samples were taken to see the differences after applying EFB compost. The observation of tomato growth were monitored for 2 months, and it was found that 40 g of EFB compost gave the highest yield with good tomato growth. Significant correlation of the soil pH, CEC and macro-micronutrients values suggest that EFB compost is suitable to improve the yield tomatoes.